2021
DOI: 10.1002/sctm.20-0496
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Micro-Grafts Enhance Tendinopathy Healing in Ovine Model: An in Vivo Experimental Perspective Study

Abstract: In Europe, approximatively 100 000 to 500 000 tendon repairs are performed every year. These procedures are associated with a considerable rate of postoperative complications (from 6% to 11%). Autologous micro-grafts (AAMG) and stromal vascular fraction (SVF) have been shown to improve tendon healing in 60% to 70% of treated rodents. The purpose of this study was to evaluate the effects of AAMG in a sheep model with tendinopathy. We used sheep models because, as a large animal, they are more comparable to huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 85 publications
(183 reference statements)
0
21
0
Order By: Relevance
“…MSCs are located in the bone marrow, adipose tissue, synovial membrane and muscular tissue, exerting an immunosuppressive, anti-inflammatory, and antifibrotic effect. Tissue engineering considers adopting MSCs as an option for regenerating tissues, with reference to bone and cartilage, due to their ability to differentiate into multiple cytotypes, including chondrocytes and osteoblasts [ 18 , 19 ], but MSCs are also able to heal the damaged tendon [ 20 ]. Therefore, the “stromal vascular fraction” (SVF), which is mainly located around blood vessels, is a heterogeneous solution stemmed from adipose tissue and composed by adipose stem cells (ASCs), endothelial cells, and stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are located in the bone marrow, adipose tissue, synovial membrane and muscular tissue, exerting an immunosuppressive, anti-inflammatory, and antifibrotic effect. Tissue engineering considers adopting MSCs as an option for regenerating tissues, with reference to bone and cartilage, due to their ability to differentiate into multiple cytotypes, including chondrocytes and osteoblasts [ 18 , 19 ], but MSCs are also able to heal the damaged tendon [ 20 ]. Therefore, the “stromal vascular fraction” (SVF), which is mainly located around blood vessels, is a heterogeneous solution stemmed from adipose tissue and composed by adipose stem cells (ASCs), endothelial cells, and stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…SVF, a product of adipose tissue, carries a wide variety of cells, including endothelial cells, preadipocytes, type 2 macrophages, T cells, pericytes as well as mesenchymal stromal/stem and progenitor cells [ 89 , 90 , 94 ]. The application of SVF for the treatment of tendinopathies, specifically, yields satisfactory regenerative outcomes [ 95 , 96 , 97 , 98 ]. An in vivo study with SVF and AD-MSCs demonstrates the maintenance and induction of tendon fiber organization [ 96 ].…”
Section: Orthobiologics In Atmentioning
confidence: 99%
“…The application of SVF for the treatment of tendinopathies, specifically, yields satisfactory regenerative outcomes [ 95 , 96 , 97 , 98 ]. An in vivo study with SVF and AD-MSCs demonstrates the maintenance and induction of tendon fiber organization [ 96 ]. Usuelli et al demonstrated that the intratendinous SVF injection exhibited faster recovery results at just 15 days after treatment for AT [ 95 ].…”
Section: Orthobiologics In Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, they downregulate relevant inflammatory factors, enhance fibroblast proliferation, accelerate tendon cell differentiation, and boost angiogenesis. Finally, they further spur tissue regeneration and boost the process of tendon repair ( Shen et al, 2020 ; Piccionello et al, 2021 ). While MSCs have considerable benefits in musculoskeletal disorders, there is still a certain risk of infection during the healing process.…”
Section: Characteristics and Merits Of Lllt For Tendon Injuries In Cl...mentioning
confidence: 99%